Los procesos cognitivos básicos y la comprensión lectora en estudiantes de primer ciclo de la carrera de Contabilidad y Auditoría, paralelo “B” de la Facultad Jurídica, Social y Administrativa, 2023-2024 - Valarezo Carrión, Adriana Katherine (2024)
The aim of this curricular integration study was to examine the correlation between the levels of basic cognitive processes involving attention and memory, and the levels of reading comprehension among first-cycle students enrolled in the Accounting and Auditing program, parallel "B," within the Faculty of Legal, Social, and Administrative Sciences, during the period of 2023-2024. Given the considerable significance of this relationship within the context of higher education, this research serves as a valuable contribution to future endeavors, particularly considering the scarcity of available information in this field. The study employed a correlational and cross-sectional approach, utilizing a non-experimental design. The sample comprised 22 students studying Accounting and Auditing. The d2 test was employed as a measure of attention, while the memory subscale of the RIAS test assessed memory. Additionally, the ICLAU instrument was utilized to gauge reading comprehension. Pearson's non- parametric correlation coefficient was applied to quantify the association between variables, acknowledging the ordinal nature of the data. The findings revealed a moderate negative correlation, suggesting a lack of significant connection between attention and reading comprehension. Conversely, a moderate correlation was observed between memory and reading comprehension, indicating a notable relationship between these variables. In summary, it is deduced that the correlation with attention and memory is restricted, implying the presence of other influential factors impacting reading comprehension.